LA PLANEACIÓN ESTRATÉGICA COMO FACTOR DE COMPETITIVIDAD EN LAS EMPRESAS FAMILIARES DEL SECTOR COMERCIAL DEL VALLE DE MEXICALI - Montoya, Mariana Monserrat Valenzuela; Torres, Virginia Guadalupe López; Moreno, Luis Ramón Moreno (European Scientific Journal, ESJ, 2015)
The family business plays an important role in the economic and social environment in Mexico, it is estimated that 90% of the country’s businesses are family owned and managed. However, often present serious problems of continuity due to the many deficiencies they present, the lack of planning being the most prominent. This investigation surveyed 69 companies in the commercial sector of the Mexicali Valley in order to determine the role of strategic planning in these companies as a factor to boost their competitiveness. According to the results only 21% perform strategic planning processes, 15% say SWOT analysis, so the impact of strategic planning on the competitiveness is very poor. So it is necessary to promote the implementation of strategic plans and design strategies to enable them to create competitive advantages.